5,000 awesome facts (about everything!) 3. - National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2016)
More fun than a barrel of monkeys and more interesting than reality TV-- this brain candy-filled book is an explosion of information about sensational topics kids love: royalty, gravity, bioluminescence, sloths, wildfires, bubblegum, cars, breakfast, aliens, you name it! It's a fantastic, fact-filled edition with all-new info on hundreds of topics, and the same great design that captures kids' attention and keeps them yearning for more.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes index.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Curiosities and wonders -- Juvenile literature; Handbooks, vade-mecums, etc. -- Juvenile literature; Electronic books- OSLIS